Determinants of Friendship in Social Networking Virtual Worlds - Chesney, T.; Chuah, S.; Hui, Wendy; Hoffmann, R.; Larner, J. (Association for Information Systems, 2014)
This paper examines the determinants of friendship between two users in a virtual world who are unaware of each other's real identities. Drawing on theories of homophily, heterophily and propinquity, three virtual world behaviours are analysed: avatar appearance, avatar location, and avatar communication. Data are collected on 179 participants interacting in a novel virtual world. The main results show that: (1) avatars did not tend to form friendships with avatars that are similar in appearance to themselves but did tend to form friendships with avatars that are dressed differently from themselves; (2) in terms of location, the closer an avatar stands to other avatars, the more likely the avatar is to receive a friend invitation; and (3) the fewer words an avatar uses in communication, the more likely the avatar is to receive a friend invitation. This paper contributes to theories of virtual world interaction and to using virtual worlds as a data collection platform.